Legal and Policy Frameworks for Climate and Air Protection in Saudi Arabia: A Review of Progress - Albakjaji, Mohamad; Alhussein, Hussein Shahada; Baroudy, Jinane El (Journal of Posthumanism, 2025)
This research paper analytically examines Saudi Arabia's climate protection strategies, focusing on studying the pivotal role of environmental regulations, programs, and initiatives‎ in the Kingdom of Saudi Arabia in improving air quality and mitigating climate change. The study also analyzes the role of Saudi policy in addressing climate change, considering the nation's unique environmental context and economic structure. The study also concludes with some recommendations aimed at enhancing the efficiency of current regulatory frameworks.